Hypertension Prevention Education as a Promotive and Preventive Effort in the Community in Sunggumanai Hamlet - Syarfaini, Syarfaini; Jastam, Muh. Saleh; Wahyuddin, Nur Rahmah; Yuslikha, Futihat Rizki; Olivia, Dian Zahra; Nurfadilla, Nurfadilla; Adha, Andi Syamsiah (Unihealth Community Research, 2026)
Hypertension is a non-communicable disease that remains a major public health problem due to its high prevalence and low detection rate. Limited community knowledge regarding risk factors and hypertension prevention contributes to increased cardiovascular complications. This community service activity aimed to improve public knowledge about hypertension prevention through health education. The program was conducted in Sunggumanai Hamlet, Belapunranga Village, Gowa Regency, involving 30 community members. The method applied was interactive lectures supported by visual media and discussions, accompanied by pre-test and post-test assessments to measure knowledge levels. The results indicated a significant improvement in participants’ knowledge. Prior to the intervention, 90.0% of respondents had low knowledge, while after the education session, 96.7% demonstrated adequate knowledge. Statistical analysis using the Wilcoxon test showed a significant difference before and after the intervention (p=0.000). These findings indicate that health education is effective in increasing community knowledge regarding hypertension prevention. Continuous and sustainable educational programs are recommended to support long-term healthy lifestyle changes in the community.